Effect of microstructure on the magnetostriction properties of Fe81Ga19−xAlx alloys obtained by melt spinning. (January 2022) - Yao, Te; Gong, Pei; Li, Hua; Wei, Zongying; Li, Xiao; Jiao, Peiying
Highlights: I investigated the effect of Al addition on the microstructure and magnetostriction of melt-spun Fe81Ga19 alloy thin strips. And the results indicated that Al addition can refine the grains of Fe81Ga19−xAlx alloys. When higher content of Al is added to Fe-Ga alloy, the fluidity of liquid alloy will be reduced. The saturation magnetostrictive coefficient of the Fe81Ga18.8Al0.2 alloy thin strip was 343 ppm, which was significantly higher than that of the as-cast alloy. The amorphization of the M-D03 phase is affected by both Al addition and rapid cooling. When the aluminum content (i.e. Fe81Ga19−xAlx) is less than 6at%, a(A2), a(D03) and I200 (A2, D03)/I110 (A2, D03) change with the increase of aluminum content. Abstract: Fe81 Ga19− x Al x ( x  = 0.2, 0.5, 3, 6, 9) alloy thin strips are obtained by melt spinning in a non-consumable arc furnace to investigate the effect of Al addition on the microstructure and magnetostriction properties of melt-spun Fe81 Ga19 alloy thin strips. The results indicate that the addition of Al can refine the grains of Fe81 Ga19− x Al x alloys . The melt-spun Fe81 Ga19− x Al x alloy thin strips were composed of A2 phases and many amorphous phases, while modified D03 phase was also produced. The saturation magnetostrictive strain coefficient of the Fe81 Ga18.8 Al0.2 alloy was 343 ppm, which was significantly improved compared to the as-cast alloy. The analysis of the experimental data indicated that rapid quenching and Al addition led to relaxation of the crystal structure. Specifically, the coupling strength between the atoms of the Fe81 Ga19− x Al x alloy thin strips decreased slightly, which was the main reason for the increase in the saturation magnetostrictive strain of the alloy thin strips. Graphical abstract: Graphical abstract Image, graphical abstract